Formulation and Evaluation of Natamycin Solid Dispersion Incorporated Ophthalmic Films - Bhandari, Lavanya; Patil, Archana S; Bolmal, Udaykumar; Masareddy, Rajashree; Dandagi, Panchaxari (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: The aim of this study was to enhance the solubility of Natamycin, an antifungal agent used in fungal keratitis, through solid dispersion incorporated ophthalmic films with the purpose to avoid frequent dosing, enhance the period of retention, and sustaining release for better patient compliance. Materials and Methods: Firstly, solid dispersions were prepared by the solvent evaporation method and then, the best solid dispersion formulation was incorporated into films which were prepared by the solvent casting method using retarding polymers Ethyl cellulose, PVA and Chitosan. PEG-400 was used as a plasticizer. The films were evaluated for their thickness, surface pH, drug content, weight uniformity, folding endurance, tensile strength, antimicrobial activity, in-vitro and ex-vivo permeation studies, and in-vitro antifungal studies. Results and Discussion: The films exhibited good mechanical properties with promising results and were in an acceptable range. The optimized formulation NF6 shows more drug release in in-vitro studies as compared to ex-vivo. This is due to the varying pore size of the cornea and disturbance of other tissues. An ocular irritation test revealed that the prepared formulation was non-irritant. Conclusion: Thus, the formulated ophthalmic film seems to be a promising formulation for the safe and effective delivery of Natamycin through the ocular route in the treatment of fungal keratitis.
Keywords: Ophthalmic films; Natamycin; Ethyl cellulose; PVA; Chitosan